Ditylenchus sarvarae sp. n. (Tylenchina: Anguinidae) from Iran - Shokoohi, Ebrahim; Iranpour, Fahime; Peneva, Vlada; Elshishka, Milka; Fourie, Hendrika; Swart, Antoinette (Zootaxa, 2018)
During a survey of soil nematodes in Iran, a new species of Ditylenchus Filipjev, 1936 was discovered. Ditylenchus sarvarae sp. n. is characterised by its body length (1.0–1.4 mm), lateral field with seven incisures and without areolation, long postuterine sac (1.8–2.8 times the corresponding body diameter) and conical female tail with pointed tip (68–89 μm long, c = 13.7–18.2, c’ = 4.2–5.1). Male specimens have conical tails (64–70 μm long, c = 14.5–16.7, c’ = 4.0–4.5), spicules (22–26 μm long) and gubernaculum (8–10 μm long). Measurements and illustrations are provided for this new species. A molecular study of the 28S rDNA region of D. sarvarae sp. n. demonstrates that the Iranian species belongs to a separate group compared with the other molecularly characterized species of genus Ditylenchus.